Chinese Art at the End of the Millennium : Chinese-art.com : 1998-1999 - Clark, John (Hong Kong : New Art Media Limited, 2000)
Weiwei, Ai ; Guoqiang, Cai ; Jin, Cai ; Yi, Ding ; Wenda, Gu ; Lei, Hong ; Xiaojun, Wu ; Yongping, Huang ; Xiaodong, Liu ; Wei, Liu ; Liuming, Ma ; Dong, Wei ; Tilton, Jack ; Nanxing, Xie ; Bing, Xu ; Mian, Yang ; Wang, Zhan ; Peili, Zhang ; Xiaogang, Zhang ; Tiehai, Zhou ; Hui, Zhuang
boek
Keywords: China